Infant baptism debate in early Christianity - Van De Beek, A (Nederduitse Gereformeerde Teologiese Tydskrif, 2009)
Research on infant baptism in early Christianity usually focuses on the question where its presence can be proved. This article deals with the question: where is it contested? It turns out that only Tertullian and Gregory of Nazianza have texts wherein they plea for a delay of baptism. Both, however, also have strong positive texts about infant baptism. The passages about delay are in the framework baptizing catechumens, not about children of Christians. Thus, there is no text in early Christianity against baptism of the children of believers. Pelagius should draw this conclusion from his theology, according to Augustine, but he does not dear so because of the protests it would evoke. As new customs were usually contested in early Christianity, we can safely draw the conclusion that infant baptism was normal use in that time.